3. DETENTION OF FOREIGN NATIONALS IN THE SEMARANGBANGLADESHI FAKE VISA CASE AS AN IMPLEMENTATION OFIMMIGRATION LAW ENFORCEMENT IN INDONESIA - Virda Anika Wahyuni; Nur Priyanto; Suroso; Anwar Hendro; Hendri Himawan; Tutidikatama; Muchammad Furqon (Jurnal TNI Angkatan Udara, 2026)
This study aims to analyze detention practices regarding foreign nationals (WNA)in the case of a forged visa used by Ruhilul Amin, a Bangladeshi national who enteredIndonesia using documents inconsistent with immigration databases; the discrepancy was onlydetected when he applied for a residence permit extension at the Class I Special ImmigrationOffice (TPI) in Semarang. Findings indicate that multi-layered administrative checks—includingvisa code verification, document metadata analysis, and biometric screening—served as theprimary mechanisms for identifying data mismatches that pointed to suspected documentforgery. The study also highlights the pivotal role of "Operation Jagratara Phase II" in identifyingRA as the sole violator subjected to *pro justicia* proceedings, with detention utilized as anadministrative instrument to ensure the continuity of the investigation in accordance with LawNumber 6 of 2011 concerning Immigration. Employing a descriptive qualitative approach andthe theoretical framework of Global Governance, the study concludes that immigration lawenforcement relies on the integration of digital checks, field operations, and detention authority;it further emphasizes the need to strengthen data-based verification systems to minimizeopportunities for document forgery within modern migration systems.